2018
DOI: 10.3389/fimmu.2018.02346
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchopulmonary Aspergillosis–A Luminal Hypereosinophilic Disease With Extracellular Trap Cell Death

Abstract: Allergic bronchopulmonary aspergillosis (ABPA) is characterized by an early allergic response and late-phase lung injury in response to repeated exposure to Aspergillus antigens, as a consequence of persistent fungal colonization of the airways. Here, we summarize the clinical and pathological features of ABPA, focusing on thick mucus plugging, a key observation in ABPA. Recent findings have indicated that luminal eosinophils undergo cytolytic extracellular trap cell death (ETosis) and release filamentous chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 111 publications
(156 reference statements)
0
41
0
1
Order By: Relevance
“…Both IL‐5 and IL‐13 are produced by TH‐2 cells and are key activators of eosinophils and IgE production. In this context, repeated A fumigatus exposure in sensitized patients may lead to massive accumulation of eosinophils and activated TH‐2 cells in the bronchial lumen that results in bronchial impaction, a hallmark of severe asthma and ABPA . Considerable evidence indicates that IgE sensitization to A fumigatus and/or colonialization of the respiratory tract by A fumigatus in asthmatic patients is associated with reduced lung function and severe disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both IL‐5 and IL‐13 are produced by TH‐2 cells and are key activators of eosinophils and IgE production. In this context, repeated A fumigatus exposure in sensitized patients may lead to massive accumulation of eosinophils and activated TH‐2 cells in the bronchial lumen that results in bronchial impaction, a hallmark of severe asthma and ABPA . Considerable evidence indicates that IgE sensitization to A fumigatus and/or colonialization of the respiratory tract by A fumigatus in asthmatic patients is associated with reduced lung function and severe disease .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, repeated A fumigatus exposure in sensitized patients may lead to massive accumulation of eosinophils and activated TH-2 cells in the bronchial lumen that results in bronchial impaction, a hallmark of severe asthma and ABPA. 41,42 Considerable evidence indicates that IgE sensitization to A fumigatus and/or colonialization of the respiratory tract by A fumigatus in asthmatic patients is associated with reduced lung function and severe disease. 2,43,44 The important role of sIgE in response to A fumigatus is further highlighted by several clinical studies that show omalizumab as an interesting therapeutic strategy in ABPA, since it is associated with fewer side-effects compared to long-term corticosteroids.…”
Section: Ta B L E 3 Mrna Expression Changes In Sputum Cellsmentioning
confidence: 99%
“…Another recent study demonstrated that EETosis‐mediated CLCs directly promote inflammasome activation, Th2 lymphocyte priming, IgE synthesis and possible mucus plug formation in patients with asthma and patients with chronic rhinosinusitis (Persson et al., 2019). Thus, the pathological consequence of sialodochitis fibrinosa appears analogous to these “luminal hypereosinophilic diseases” (Ueki, Hebisawa, Kitani, Asano, & Neves, 2018).…”
Section: Figurementioning
confidence: 99%
“…The pathogenesis of ABPA is attributed to mucoid impaction of the bronchi with fungal hyphae, eosinophilic pneumonia or bronchitis, and bronchocentric granulomatosis with tissue eosinophilia [13]. In the airways, septated hyphae with acute dichotomous branching is seen in the lumen without invasion of the mucosa.…”
Section: Pathogenesismentioning
confidence: 99%